SISTEM PAKAR DIAGNOSA PENYAKIT TANAMAN JAGUNG MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - rudjiono, daniel; Setiyo Adi Nugroho; Agus Priyadi; Aprilia Ferawati Ndaumanu (STEKOM PRESS, 2024)
Abstract - Corn plants are one of the plants that are easy to grow and relatively fast to get results but also a plant that is vulnerable to pests and diseases. The symptoms that arise require an expert or agricultural expert to be able to diagnose. Limited time and expert labor is one of the causes of delayed diagnosis, causing a decrease in farmers' yields. This is the basis for making this expert system by adopting knowledge from agricultural experts about the symptoms of corn disease using the Forward Chaining method. To support the research conducted, researchers used the Research and Development (R&D) research method and the design used the Object Oriented Programming (OOP) method using the Unified Modeling Language (UML). Software is built using the PHP programming language, MySQL as a database, and Bootstrap as an interface design with a web-based system.